Analysis of literacy-based learning media produced by primary school teacher education students - Maharani Putri Kumalasani; Dian Ika Kusumaningtyas (Universitas Muhammadiyah Malang, 2024)
Literacy is an important skill that every learner must have because a large part of the educational process depends on literacy skills and awareness. It is important to be able to implement literacy using various types of literacy media, one of which is literacy media in the form of teaching aids. This study aims to analyze learning media products that have been made by students, especially teaching aids based on learning media criteria and oriented to literacy activities. This research uses a qualitative research model with a descriptive method that uses Miles and Huberman data analysis. The instruments used in this research are interview instruments and data documentation related to literacy media. The results of this study show that various types of teaching aids can be used in literacy learning. Literacy-oriented teaching aids can be an effective solution to help literacy activities in an easier, more interesting, fun, and effective way. The various types of teaching aids can perform the function of media well and support the literacy skills that must be mastered (reading, speaking, listening, and writing).